2011
DOI: 10.1021/jp109563s
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Structure and Lipid Dynamics in a Model Stratum Corneum with Oleic Acid

Abstract: The stratum corneum is the uppermost layer of the skin and acts as a barrier to keep out contaminants and retain moisture. Understanding the molecular structure and behavior of this layer will provide guidance for optimizing its biological function. In this study we use a model mixture comprised of equimolar portions of ceramide NS (24:0), lignoceric acid, and cholesterol to model the effect of the addition of small amounts of oleic acid to the bilayer at 300 and 340 K. Five systems at each temperature have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 50 publications
5
75
0
1
Order By: Relevance
“…Therefore, both arrangements are, in principle, still possible. The experimental results we obtained using synthetic lipid materials are in accordance with the theoretical simulation studies of SC lipid mixtures where it was shown that CER NS shows significant interdigitation at the center of the unit cell, and with the CHOL headgroups located close to the water-lipid interface (51,52).…”
Section: Molecular Model Of the Sppsupporting
confidence: 86%
“…Therefore, both arrangements are, in principle, still possible. The experimental results we obtained using synthetic lipid materials are in accordance with the theoretical simulation studies of SC lipid mixtures where it was shown that CER NS shows significant interdigitation at the center of the unit cell, and with the CHOL headgroups located close to the water-lipid interface (51,52).…”
Section: Molecular Model Of the Sppsupporting
confidence: 86%
“…However, the frequency of water permeation events was found to double, indicating some OA-induced permeability enhancement. Recently Hoopes et al 43 studied the effect of OA on the mixed 1 : 1 : 1 CER2-CHOL-FA skin lipid bilayer at the OA concentrations up to 0.1 mol% and T = 300 and 340 K. Similar to the OA-DPPC study discussed above, 42 no significant changes in the properties of the skin lipid bilayer upon addition of OA were observed. Addition of a small amount of OA leads to slight enhancement in the diffusion of cholesterol, the fastest species in this gel-like mixture, which in turn increases the diffusion of ceramide and fatty acid.…”
Section: Introductionmentioning
confidence: 87%
“…It is important here to note that our belief is not that eczema is borne solely from the occlusion of sweat ducts by staphylococcalderived biofilm, but as elucidated in our previous work, that eczema develops secondary to a "double-hit phenomenon. " [25] In atopic dermatitis, the first hit is a genetic one-in the form of filaggrin (or other gene) deficiency. It is the biofilm-occluded sweat ducts that constitute an environmental second hit which in turn permits activation of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these disruptive factors are as follows: granules in granular parakeratosis, fungi in tinea pedis, and yeast organisms (especially Malassezia oleosa) in adultonset Seborrheic dermatitis. It has been reported that certain Malassezia species produce oleic acid, a molecule that, in experimental models, has been shown to alter the properties of the Stratum corneum [25]. Thus, in these diseases, the genetic hit is replaced by another environmental hit that results in a similar defect in the Stratum corneum.…”
Section: Discussionmentioning
confidence: 99%